Different Sensitivity of Macrophages to Phospholipidosis Induction by Amphiphilic Cationic Drugs - Öhlinger, Kristin (Int J Mol Sci, 2020)
Phospholipidosis (PLD), the intracellular accumulation of phospholipids, is an adaptive response to toxic stimuli and serves as an important parameter in the biological assessment of compounds. Cationic amphiphilic drugs are the main inducers of PLD and may impair the function of alveolar macrophages. In vivo and in vitro models are used for PLD screening but the choice of the cellular model may be important because PLD develops in a cell- and species-specific manner. In this study, a panel of different staining (LysoSensor, Acridine Orange, Nile Red, HCS LipidTOX, LysoID) was evaluated in murine (DMBM-2, J774, RAW264.7) and human (THP-1, monocyte-derived macrophages from peripheral blood) cells to identify the most sensitive and easy to analyze staining method and to detect species-specific differences in the reaction pattern. Amiodarone and chloroquine served as inducers of PLD. High content screening was used to compare number, area, and intensity of the staining. Due to the fast staining protocol and the sensitivity of the detection, LysoID proved to be the most suitable dye of the testing. The lower induction of PLD by chloroquine reported in vivo was also seen in this study. THP-1 macrophages, followed by DMBM-2 cells, produced the most similar reaction pattern to human monocyte-derived macrophages.